2014
DOI: 10.1155/2014/896587
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of the Cost-Effectiveness of Nurse Practitioners and Clinical Nurse Specialists: What Is the Quality of the Evidence?

Abstract: Background. Improved quality of care and control of healthcare costs are important factors influencing decisions to implement nurse practitioner (NP) and clinical nurse specialist (CNS) roles. Objective. To assess the quality of randomized controlled trials (RCTs) evaluating NP and CNS cost-effectiveness (defined broadly to also include studies measuring health resource utilization). Design. Systematic review of RCTs of NP and CNS cost-effectiveness reported between 1980 and July 2012. Results. 4,397 unique re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 83 publications
1
39
0
2
Order By: Relevance
“…We updated the database search by repeating it for the period of 31 July 2012 to 31 July 2013. More details about the search strategy can be found elsewhere [20].…”
Section: Information Sources and Searchmentioning
confidence: 99%
“…We updated the database search by repeating it for the period of 31 July 2012 to 31 July 2013. More details about the search strategy can be found elsewhere [20].…”
Section: Information Sources and Searchmentioning
confidence: 99%
“…Multiple systematic reviews have demonstrated the effectiveness of APN roles for improving patient health and quality of care and reducing healthcare utilization and costs (Bryant‐Lukosius et al., ; Donald et al., ; Newhouse et al., ). These studies also indicated a need for conceptually stronger evaluation designs to improve the quality of research and to address knowledge gaps about cost effectiveness and how APN roles contribute to improved patient, provider, and health system outcomes (Donald et al., ; Marshall et al., ). There is also a need for research to evaluate the impact of nonclinical APN role activities (e.g., leadership, research; Bryant‐Lukosius, DiCenso, Israr, & Charbonneau‐Smith, ).…”
Section: Introductionmentioning
confidence: 99%
“…However, in the context of this work, where the main focus is on the implementation of the clinical nurse specialist role, the existent reviews present some limitations. Most of them do not differentiate between different types of APNs (NPs and CNSs) (Donald et al;Tsiachristas and de Bont, 2015) or are specifically focused on NPs (Martínez-González et al, 2014a;Newhouse and Heindel, 2011). Additionally, some are outdated (Fulton and Baldwin, 2004) or strictly focused on a specific type of care (such as primary care), on a specific type of ef-fects (such as health outcomes or economic effects), or only dedicated to a specific type of CNSs (certified nurses, for example) (Martínez-González et al, 2014b;Whitehead, 2019).…”
Section: Why? the Empirical Evidencementioning
confidence: 99%